Adamantyl and carbazole containing trans-poly(norbornene-dicarboximide)s as electro-optic chromophore hosts. (20th May 2019) - Spring, Andrew M.; Qiu, Feng; Hong, Jianxun; Bannaron, Alisa; Cheng, Xiaoyang; Yokoyama, Shiyoshi
Abstract: A selection of trans -poly(norbornene-dicarboximide) random copolymers incorporating adamantyl and carbazole groups have been prepared using the Grubbs 1st generation catalyst. The copolymer with the greatest carbazole content was employed as a host for a high activity chromophore guest. The adamantyl groups were able to elevate the glass transition and thermal decomposition temperatures of the host copolymers, while the carbazole groups were included to facilitate the dispersion of the added chromophores and enhance the poling process. The mass of the adamantyl pendant monomer was kept constant as the mass of the carbazole pendant monomer was increased gradually. The successful incorporation of the carbazole moiety into the copolymers was confirmed by 1 H NMR integration. The polymers had a predominantly trans microstructure and the cis / trans ratio did not change significantly. The polymer molecular weights increased linearly from 25, 758 g/mol to 56, 827 g/mol as more carbazole-pendant monomer was incorporated. Polydispersities ranged from 1.29 to 1.70 and elemental analysis confirmed an ascending carbon% in the polymers from 72.29% to 76.26%. The glass transition temperatures decreased from 240 °C to 126 °C, with the thermal decomposition temperatures (10% loss) remaining relatively constant at between 423 °C to 394 °C, indicating the polymers had a good thermal stability. The chromophore guest concentration was increased gradually into the copolymer host from 15 wt% to 65 wt%. When poled at a field of 50 V/μm in thin film it was found that the optimum poling temperature decreased linearly from 150 °C to 90 °C as the chromophore concentration was increased, a maximum poling efficiency of 1.02 was achieved at a chromophore concentration of 55 wt%. Graphical abstract: Image 1 Highlights: Random copolymers containing pendant adamantyl and carbazole groups. High polling efficiency electro-optic guest-host system. Ring opening metathesis polymerization of functionalized NDI monomers. High glass transition and thermal decomposition temperature materials.